Viva Vigan! ([Vigan, Ilocos Norte Vigan Tourism Council)
Documentary on the history of the foundation of Vigan, featuring its Heritage Village, churches and its status as a World Heritage Site. Aside from monumental structures, its pre-colonial crafts and industries - pottery, hand-weaving, wood furniture-making and tile-making - are highlighted.
Produced during the administration of Eva Marie S. Medina, mayor, Liborio Arca, vice mayor, Sangguniang Bayan members, in cooperation with the Vigan Municipal Personnel Multi-Purpose Cooperative, Save Vigan Ancestral Homeowners Association (SVHAI) and the Vigan Tourism Council.
Keywords: History; Vigan -- Geography; Vigan -- Travel and description